A diverse assemblage of reef corals thriving in a dynamic intertidal reef setting (Bonaparte Archipelago, Kimberley, Australia). - Zoe T Richards; Rodrigo A Garcia; Carden C Wallace; Natalie L Rosser; Paul R Muir (PLoS ONE)
The susceptibility of reef-building corals to climatic anomalies is well documented and a cause of great concern for the future of coral reefs. Reef corals are normally considered to tolerate only a narrow range of climatic conditions with only a small number of species considered heat-tolerant. Occasionally however, corals can be seen thriving in unusually harsh reef settings and these are cause for some optimism about the future of coral reefs. Here we document for the first time a diverse assemblage of 225 species of hard corals occurring in the intertidal zone of the Bonaparte Archipelago, north western Australia. We compare the environmental conditions at our study site (tidal regime, SST and level of turbidity) with those experienced at four other more typical tropical reef locations with similar levels of diversity. Physical extremes in the Bonaparte Archipelago include tidal oscillations of up to 8 m, long subaerial exposure times (>3.5 hrs), prolonged exposure to high SST and fluctuating turbidity levels. We conclude the timing of low tide in the coolest parts of the day ameliorates the severity of subaerial exposure, and the combination of strong currents and a naturally high sediment regime helps to offset light and heat stress. The low level of anthropogenic impact and proximity to the Indo-west Pacific centre of diversity are likely to further promote resistance and resilience in this community. This assemblage provides an indication of what corals may have existed in other nearshore locations in the past prior to widespread coastal development, eutrophication, coral predator and disease outbreaks and coral bleaching events. Our results call for a re-evaluation of what conditions are optimal for coral survival, and the Bonaparte intertidal community presents an ideal model system for exploring how species resilience is conferred in the absence of confounding factors such as pollution.